2018
DOI: 10.1038/s41467-018-07788-5
|View full text |Cite
|
Sign up to set email alerts
|

Hidden heterogeneity and circadian-controlled cell fate inferred from single cell lineages

Abstract: The origin of lineage correlations among single cells and the extent of heterogeneity in their intermitotic times (IMT) and apoptosis times (AT) remain incompletely understood. Here we developed single cell lineage-tracking experiments and computational algorithms to uncover correlations and heterogeneity in the IMT and AT of a colon cancer cell line before and during cisplatin treatment. These correlations could not be explained using simple protein production/degradation models. Sister cell fates were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 47 publications
7
58
3
Order By: Relevance
“…We observed moderate correlations (Pearson and Spearman rank coefficients of 0.43 and 0.51, respectively) between 11,696 reference and mother cell pairs (Figure 4D), which represents an order of magnitude higher, yet still relatively low, mother-daughter correlation compared to previously shown trends 4,7,8 . The correlations continued to decrease with increasing ancestor distance all the way to a cell's great-great-grandmother (0.24, 0.10, 0.17 for Pearson and 0.25, 0.07, 0.14 for Spearman rank coefficients).…”
Section: Deep Lineage Trees Enable Evaluation Of Correlations Of Cellcontrasting
confidence: 47%
See 3 more Smart Citations
“…We observed moderate correlations (Pearson and Spearman rank coefficients of 0.43 and 0.51, respectively) between 11,696 reference and mother cell pairs (Figure 4D), which represents an order of magnitude higher, yet still relatively low, mother-daughter correlation compared to previously shown trends 4,7,8 . The correlations continued to decrease with increasing ancestor distance all the way to a cell's great-great-grandmother (0.24, 0.10, 0.17 for Pearson and 0.25, 0.07, 0.14 for Spearman rank coefficients).…”
Section: Deep Lineage Trees Enable Evaluation Of Correlations Of Cellcontrasting
confidence: 47%
“…For example, the observed distribution of cell cycle durations in a population of cells is governed either by stochastic processes, inherited in a deterministic fashion, or some combination of both [3][4][5][6] (Figure 1A). Previous studies have shown poor correlations within lineages when observing direct ancestral relationships, but remain correlated with immediate relatives 4,7,8 . However, these studies have been performed using manually annotated data, which is laborious to acquire and limits the depth and statistical power to study more distant relationships amid noisy data.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Correlations in generation times along cell lineages have been used to study systems from cyanobacteria to cancer cells [22, 30, 32]. In particular, the relations between the parent-child, sibling-sibling, and cousin-cousin correlations in generation times ( ρ md , ρ ss , ρ cc , respectively) inform how division timing might be inherited from the parent cell or affected by an underlying clock-like process.…”
Section: Supplementary Materialsmentioning
confidence: 99%